Tachycardia-Induced Cardiomyopathy in a 1-Month-Old Infant - Joseph C. Mares; Yaniv Bar-Cohen (Case Reports in Pediatrics)
Supraventricular tachycardia (SVT) is the most common arrhythmia in children and is especially common in infants. SVT is typically thought of as an acute condition; however, if unrecognized, a persistent tachyarrhythmia can progress to a state of cardiac contractile dysfunction known as tachycardia-induced cardiomyopathy. A high index of suspicion for an underlying arrhythmia is needed in the workup of any patient with new onset heart failure, and the 12-lead electrocardiogram can aid in the diagnosis. While this may be a rare cause of dilated cardiomyopathy and heart failure in children, the condition is usually reversible and should be considered in infants and young children.